Urbanization levels are associated with the start of the dawn chorus in vermilion flycatchers in Colombia. Issue 4 (4th July 2021) - Sánchez-González, Katherin; Aguirre-Obando, Oscar A.; Ríos-Chelén, Alejandro A.
Abstract : Increased urbanization leads to the modification of animal behavior, including the start of the dawn chorus in birds. The beginning of the dawn chorus has been studied in relation to the level of urban noise and nocturnal artificial light in oscine birds, with few studies in suboscines. We evaluated a possible relationship between the start of the dawn chorus and different urbanization levels in a suboscine, the vermilion flycatcher ( Pyrocephalus rubinus ), in seven locations in the city of Armenia (Colombia). We categorized the urbanization level in each location according to its percentage of built structures, into low and high levels. Observations were made during pre-dawn, starting at 00:00 hr. During each visit we recorded maximum noise levels, artificial light at night (ALAN) and time of first song. Males inhabiting the high urbanization locations started the dawn chorus on average 101 min before sunrise, while males in low urbanization levels did so on average 38 min before. Neither noise level nor ALAN explained this difference. We discuss that, for suboscines, another urban-related factor (ambient temperature) may be a key factor driving the onset of dawn chorus.